Giant Phyllodes Tumor of the Breast - Fonda R.P Silalahi; Mirton (Cermin Dunia Kedokteran, 2023)
Phyllodes tumor is a benign but potentially malignant breast cancer. The incidence phyllodes neoplasm is only about 0.3%-1% of all breast malignancies. A large phyllodes tumor in a 35-year old female was reported. She had history a slowly growing mass in the right breast since 15 years ago and grew rapidly in the last 3 months. After infection control, a right mastectomy with resection of the pectoral muscle was performed followed with secondary closure of the defect with skin graft after 6 weeks. The tumor measured 46x49x24 cm in size and weight of 10.2 kg with malignant histopathological result; no evidence of local or distant recurrence after 3 month follow up.   Tumor phyllodes adalah kelainan payudara yang bersifat jinak, namun berpotensi ganas. Insiden tumor phyllodes sekitar 0,3%-1% dari semua tumor payudara. Dilaporkan kasus pada wanita berusia 35 tahun dengan tumor phyllodes yang berukuran sangat besar. Massa payudara kanan berukuran kecil yang tumbuh perlahan telah ada sejak 15 tahun. Dalam 3 bulan terakhir terjadi pertumbuhan massa yang cepat dan progresif. Setelah pengendalian infeksi, dilakukan mastektomi kanan dengan reseksi otot pektoralis. Selanjutnya dilakukan perawatan luka sekunder dan diikuti dengan penutupan defek dengan tandur kulit setelah 6 minggu. Didapatkan tumor berukuran 46x49x24 cm dan berat 10,2 kg dengan hasil histopatologi keganasan. Tidak ada bukti kekambuhan lokal atau jauh setelah 3 bulan tindak lanjut. Fonda RP Silalahi, Mirton. Tumor Phyllodes Payudara.